Idee niepodległości i suwerenności Polski w działalności informacyjno-propagandowej NSZZ „Solidarność” w Bydgoszczy w latach 1980-1989 (Kronika Bydgoska, 2020)
We can talk about the evolution of ideas proclaimed by the broadly understood Solidarity Movement, from socio-social ideas, including emancipation, through democratic and civic ideas to independence and the sovereignty of the nation and the state. The power of articulation of these ideas clearly increased after the declaration of Martial law on 13 December 1981, and ever closer to its realization after the Round Table Talks on 1989.